The circular economy and the strategic perspective of the rice sector of the Daule canton period 2021-2022 - De Lucas Coloma, Luis Alberto; Campi Mayorga, Ida Ivete; Urbina Bustos, Sonnia Soraya; Poveda Arteaga, Javier Andrés (Revista Universidad de Guayaquil, 2022)
The economic system currently has limitations in terms of its sustainability, such as: overproduction, the definition of planned obsolescence, the culture of consumption and use, as well as inefficiency for the benefit of waste in the different stages of production, They cause tensions in the rice sector that is increasing every year. Therefore, the relationship between the circular economy and the business perspective of the rice sector in the Daule canton should be analyzed for the period 2021-2022. The methodology implemented in the research has a mixed approach with a non-experimental design and a descriptive scope due to the fact that by conducting a survey aimed at companies the following results are evidenced, 70% consider that sometimes waste in the different stages of production cause tensions in the rice sector every year. Likewise, the fundamental differences that exist between the linear and circular economy, the first focuses on profitability without having any concern for the product's life cycle and the second bets on sustainability.
Keywords: Social responsibility; Projects with a social focus; Comprehensive Command Matrix